Germination of Aristolochia elegans Mast. seeds at different temperatures and concentrations of gibberellin - Guariz, Hugo Roldi; Shimizu, Gabriel Danilo; Menegon Castilho , Ítala; Paula, Jean Carlo Baudraz; Junior Ribeiro , Walter Aparecido; Sperandio, Huezer Viganô (Comunicata Scientiae, 2022)
Aristolochia elegans is a plant widely appreciated for its attractiveness, being used as an ornamental species. However, information on the germination behavior of its seeds is scarce. Thus, the objective of the current work is to evaluate the germination of seeds of A. elegans under varying conditions of temperature and concentrations of gibberellin. The seeds were immersed in gibberellin solution at concentrations of 100, 200, and 300 mg L-1, before being sown on blotting paper and transferred to germinators at constant temperatures of 15, 20, 25, 30, and 35ºC. The percentage, speed index, mean time, and germination speed were evaluated. There was no interaction effect or isolated effect of gibberellin, only an isolated effect of temperature on all parameters evaluated. For germination, a maximum response was obtained at the estimated temperature of 29.14˚C, with 75% germination, and the minimum temperature was estimated at 16.9˚C. The mean germination speed increased with increases in temperature, up to a maximum of 29ºC, and at temperatures above this value, the speed decreased. It is concluded that the temperature of 29.4˚C leads to the best germination, while at temperatures below 16.9˚C, the estimated minimum temperature, there is no seed germination. In addition, there is no effect of gibberellin on germination when doses are applied between 100 and 300 mg L-1.